1998
DOI: 10.1046/j.1365-2036.1998.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication ofHelicobacter pyloriwith lansoprazole, roxithromycin and metronidazole—an open pilot study

Abstract: INTRODUCTIONHelicobacter pylori infection is the most common cause of nonautoimmune chronic active gastritis. Almost all duodenal ulcer patients without exposure to nonsteroidal anti-in¯ammatory drugs are infected with H. pylori. It is well known that the eradication of this bacterium heals duodenal ulcers and drastically reduces the relapse rate from over 80% to less than 5% a year. 1 The current popular protocols for H. pylori eradication regimens consist of an acid suppressant (most commonly being omeprazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…So in these patients, as well as in patients with the indication ulcers, the diarrhoea might be caused partly through the use of one of the other prescribed medicines. [13][14][15] This is also demonstrated by the higher current use of oral antibiotics.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…So in these patients, as well as in patients with the indication ulcers, the diarrhoea might be caused partly through the use of one of the other prescribed medicines. [13][14][15] This is also demonstrated by the higher current use of oral antibiotics.…”
mentioning
confidence: 72%
“…Most of those regimens have diarrhoea as a commonly reported adverse event. [13][14][15] An analysis of all comedications used may lead to identification of patients at risk of developing diarrhoea while taking lansoprazole. In conclusion, this study was set up to investigate characteristics of diarrhoea and to identify the value of co-factors associated with diarrhoea in daily practice of lansoprazole users, including patients of any age with various indications, underlying diseases and use of other medicines.…”
Section: Introductionmentioning
confidence: 99%
“…In German children that were included in the study 20 % showed a primary clarithromycin resistance. This is a significantly higher percentage than in studies on German adults [427,428]. Metronidazol resistances were seen more often in children that were born in Asia or Africa (adjusted OR 2.42, 95 % CI 1.6 -3.7).…”
Section: Which Diagnostic Tests Are Suitable?mentioning
confidence: 60%
“…Side effects increase significantly with treatment duration exceeding 10 days. • The data currently available are not sufficient to prove the equivalence with clarithromycin of other macrolides like azithromycin [23,24] or roxithromycin [25]. • The highest cure rates are achieved with two combinations: PPI-clarithromycin-metronidazole, and PPI-clarithromycin-amoxicillin (Table 1).…”
Section: Healing and Preventing Du By Hp Eradicationmentioning
confidence: 97%